Understanding functionality of sucrose in biscuits for reformulation purposes. Issue 14 (6th August 2019) - van der Sman, R. G. M.; Renzetti, S.
ABSTRACT: We review the functionality of sucrose during the manufacture of biscuits from the perspective of sugar replacement. Besides to providing sweetness, sucrose has important functionalities concerning structure and texture formation. These functionalities also need to be mimicked in reformulated biscuits. First, we review the hypotheses concerning the development of structure and texture of biscuits during manufacturing, which are conveniently summarized in a qualitative way using the Complex Dispersed Systems methodology. Subsequently, we represent the changes of the state of the biscuit during manufacturing in the supplemented state diagram, which indicates the important phase transitions occurring during mixing and baking. We propose that when reformulated biscuits follow similar paths in the state diagram, similar structures and textures can be obtained. Physical theories exist for predicting these phase transitions for existing sucrose-rich biscuits and also reformulated biscuits containing extensive sweeteners as sugar replacers. More accurate predictions of structure and texture can be eventually obtained if they are combined with computational models, including heat and moisture transfer.